(untitled) (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2021)
Among the consequences of the Covid-19 pandemic is the potential occurrence of the so-called lost generation chiefly at the age of children. This phenomenon is marked by a certain generation’s loss of direction in life, including the process of acquiring knowledge and applying it in the way of thinking and daily behaviors. With a descriptive-explanatory method, the present study seeks to reveal a correspondence between the flexibility of the Indonesian Government’s measures in averting lost generation and the principle of elasticity (murūnah) inherent in the concept of maqāṣid al-sharī‘ah. First, to reduce the spread of the disease and its death toll, the Government has restricted access to, and even prohibited the gathering of congregations in, mosques. This research concluded that in this emergent circumstance applies the elasticity of the al-ḍarūriyyāt al-khams with ḥifẓ al-nafs taking precedence over ḥifẓ al-dīn. Second, given the relatively low ratio of the Covid-19 cases mainly in children, the Government has called for a "Back to School" (face-to-face learning method) campaign. This policy proved corresponding to the prioritization of hifz al-‘aql over ḥifẓ al-nafs and ḥifẓ al-dīn. Third, the Government’s decision to use Covid-19 vaccines amid public questions about the permissibility of the vaccine is also in accordance with the prioritization of ḥifẓ al-nasl over al-dīn, al-nafs, and al-‘aql. Based on the misunderstanding amid the Muslim ummah, the author also elastically recommended a further observation on the appropriateness of the nomenclature of “religion” among the other four protections of the al-ḍarūriyyāt al-khams. In a nutshel, normally, ḥifẓ al-dīn remains the top priority; however, in case of emergency, it can elastically swap places with the other four protections. It is in terms of this flexibility that lies the superiority and compassion (raḥmah) of Islamic law with maqāṣid al-sharī‘ah serving as one of its central points.